The Influence of Profitability, Leverage, Company Size, Ownership Structure and Board of Commissioners on Risk Management Disclosure - Ari Istiqomah; Andry Priharta; Riyanti Riyanti (Jurnal Indonesia Sosial Teknologi, 2024)
The research aims to analyze and determine the influence of profitability, leverage, company size, ownership structure and board of commissioners on risk management disclosure. This research was conducted using an associative quantitative research method with data analysis tools using multiple linear regression using SPSS 20 software with a population of 18 companies and a sample of 10 companies engaged in the oil and gas energy sector listed on the Indonesia Stock Exchange for the period 2018–2022. The results of this study show that leverage and company size partially have a significant effect on risk disclosure, while profitability, ownership structure and board of commissioners partially have a non-significant effect on risk management disclosure. The results of the smear test showed that the results of profitability, leverage, company size, ownership structure and board of commissioners together affected risk disclosure by 54%.